PENGARUH PENGGUNAAN HEADSET TERHADAP GANGGUAN PENDENGARAN: TINJAUAN TERKINI DARI SATU DEKADE TERAKHIR - Triansyah, Irwan; Ade Teti Vani; Nadia Purnama Dewi; Aryaldy Zulkarnaini; Dessy Abdullah; Yanti Fitri Yasa; Muhammad Ivan (Yayasan Nusantara Hasana Berdikari, 2025)
Headset usage has become increasingly common today, facilitating work and communication. However, prolonged use of headsets, especially at high sound frequencies, can damage the hair cells in the cochlea, leading to permanent hearing loss. This condition is known as Noise-Induced Hearing Loss (NIHL). This research employed a literature review of journals published between 2013 and 2025. The journals were searched using keywords such as